2015
DOI: 10.1007/s10608-015-9713-5
|View full text |Cite
|
Sign up to set email alerts
|

Linking Sleep Disturbance and Maladaptive Repetitive Thought: The Role of Executive Function

Abstract: Although sleep disturbance has been linked to maladaptive repetitive thought, a process commonly observed in anxiety and related disorders, the mechanism that may account for this association has not been fully elucidated. The current study used structural equation modeling to evaluate the relationship between sleep disturbance and maladaptive repetitive thought in a large sample (n = 341) to examine whether executive function partially accounts for this relationship. Consistent with predictions, results revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 83 publications
0
16
0
4
Order By: Relevance
“…Several studies have also linked self-reported AC to levels of repetitive negative thinking (RNT), including rumination and worry. These studies consistently indicate that poorer attentional control is associated with higher levels of RNT (Cox, Ebesutani, & Olatunji, 2016; Hsu et al, 2015; Mills et al, 2016).…”
Section: Introductionmentioning
confidence: 64%
“…Several studies have also linked self-reported AC to levels of repetitive negative thinking (RNT), including rumination and worry. These studies consistently indicate that poorer attentional control is associated with higher levels of RNT (Cox, Ebesutani, & Olatunji, 2016; Hsu et al, 2015; Mills et al, 2016).…”
Section: Introductionmentioning
confidence: 64%
“…This result was confirmed by Bartel, Gradisar and Williamson , who reported that presleep worry likely negatively impacted sleep. It is common for adolescents’ thoughts to turn to rumination, according to Cox, Ebesutani and Olatunji , who reported a link between sleep disturbance and repetitive thoughts, such as worry. This result confirms the importance of school nurses being available to listen to adolescents’ concerns and encourage dialogue about existential thoughts even if the adolescents do not speak spontaneously about them.…”
Section: Discussionmentioning
confidence: 99%
“…This model proposes that trauma-related appraisals related to impending danger (such as 'I will be attacked again') or negative interpretations of symptoms (such as 'If I go to sleep I will not notice intruders ' (p. 330) or 'Not sleeping will damage my body') motivate the use of dysfunctional coping strategies such as staying up late because of fear of nightmares, or ruminative thoughts about the trauma, or repetitive thinking about one's emotional state (similar to brooding about feeling sad in depression, Nolen-Hoeksema, 1991), which may then interfere with sleep onset and quality (Ehlers & Clark, 2000). Consistent with this, in non-clinical populations, maladaptive repetitive thoughts have been linked to more severe sleep disturbances (Cox, Ebesutani, & Olatunji, 2016;Nota & Coles, 2015), and shown to mediate the relationship between depressed mood and sleep quality (Slavish & Graham-Engeland, 2015). Studies in clinical populations of individuals with Generalised Anxiety Disorder have also shown that the frequency of evening worry predicts subsequent sleep quality, and vice versa (Thielsch et al, 2015), and rumination following a stressor has been found to predict increased self-reported and objective sleep onset latency (Zoccola, Dickerson, & Lam, 2009).…”
Section: Introductionmentioning
confidence: 86%